Establishing the VR-haptic thinkers group: Insights and progress in dental training technologies - Szabolcs Felszeghy; Mikko Liukkonen; Nicla Flacco; Mahmoud M. Bakr; Sarah Rampf; Simona-Georgiana Schick; Maria F. Sittoni-Pino; Kristin Ackerman; Santiago Arias-Herrera; Ben Audsley; Santiya Bell; Samantha Byrne; et al. (Saudi Dental Journal)
In today’s fast-paced, digitalized world, dental educators and professionals alike need to try and stay up to date on current learning methods to provide the best possible education to the new generations of students. VR-haptic training allows educators to guide students in performing dental exercises within a digital environment using input methods with tactile force feedback features. This can reduce the mental burden of students due to fear of failure, as material losses are no longer a factor. Additionally, students can practice in their own time and pace, outside of teaching hours. Despite being digital, this mode of teaching has been shown to enable skill transfer to the real world, affording educators more flexibility with how to teach their students both before and during traditional methods of practical dental education. To help support the embracement of this new technology, a global VR-Haptic Thinkers Consortium was established in early 2024 and is now formed of 36 partner universities, institutions, and industrial companies. The second VR-Haptic Thinkers Meetup, held in mid-2024, was given the theme of “VR-Haptic Dentistry, Pedagogy, and Curriculum Evolution”. The theme of the meetup was timely as in recent years dental educators have all faced many challenges in education and research and have had to deal with rapid changes in supportive VR-haptic education. A robust program was featured to engage with the dental community members who are curious about the new technological advancements in dental education.